Collection device with collection oscillating arm of water surface cleaning boat - DONG FENGLIANG; NI JIE; WU PEISONG; HE XIAO; YANG YONG; GUO WEI; YU QIA; LIU HAO; LIU JIANQING (2015)
The invention relates to a collection device with a collection oscillating arm of a water surface cleaning boat. The collection device comprises a collection chamber, a conveying net belt which is located in the collection chamber, a driving mechanism, a collection oscillating arm, and a hydraulic oil cylinder which is used for driving the collection oscillating arm to be unfolded or folded, wherein the collection oscillating arm comprises an oscillating arm main body which is perpendicular to a water surface and a net plate which can be detachably arranged on the oscillating arm main body. The collection device further comprises an arc-shaped transition connecting plate which is located at the rear end part of the oscillating arm main body, wherein the oscillating arm main body is hinged with one side of the front end of the collection chamber through the arc-shaped transition connecting plate, and the rear end part of the oscillating arm main body can be inserted into the collection chamber. Since the rear end part of the collection oscillating arm can be inserted into the collection chamber, floating objects are not gathered at the arrangement position of the rotating shaft, the collection of the floating objects on the water surface is facilitated, the rotating shaft can be effectively prevented from being twisted by floating objects such as water plants, the collection oscillating arm can be guaranteed to be smoothly unfolded or folded, the structure is simple, the implementation is facilitated and the cost is low.